Evaluation and Origin of Residual Stress in Hybrid Metal and Extrusion Bonding and Comparison with Friction Stir Welding. (15th March 2022) - Tognan, Alessandro; Sandnes, Lise; Totis, Giovanni; Sortino, Marco; Berto, Filippo; Grong, Øystein; Salvati, Enrico
Highlights: Residual stress in HYB was evaluated for the first time Residual stress in FSW was assessed for comparison with HYB HYB weld showed a higher magnitude of tensile residual stress than FSW Higher residual stress in HYB was attributed to the presence of a filler material HYB showed more joint transverse distortion as compared with FSW Abstract: Hybrid metal and extrusion bonding (HYB) is an emerging solid-state welding technique that was developed about ten years ago. HYB exploits the fundamental idea of the well-established friction stir welding (FSW) technology, but a filler material is employed to enhance control of the microstructure and the mechanical properties of the joint. HYB and FSW allow joining to be performed at lower temperatures than classical fusion welding methods. Still, thermal gradient effects seem impossible to be entirely avoided, thus leading to residual stress within the weld region and neighbouring material. Although the FSW-induced residual stress evaluation has been extensively studied and understood, the evaluation and interpretation of HYB-induced residual stress have not been tackled so far. In the present paper, a quantitative investigation on residual stress and its origin in HYB was carried out for the first time. Specifically, a 4 mm thick AA6082-T6 HYB and a 4 mm thick AA6082-T6 FSW butt welds were considered. For the particular case of HYB, an AA6082-T4 was used as the filler material. In both cases, the full-field longitudinal residual stress was experimentally assessed using the Contour Method. The results showed that the HYB joint yields a higher magnitude of tensile residual stress compared to that of the FSW counterpart. A physical explanation for this difference in magnitude was attributed to the lower yield stress point exhibited by the filler material. Furthermore, the analysis revealed peak values of residual stress as high as 205±25 MPa and 165±15 MPa, for the HYB and FSW joint, respectively. Despite this, a similar distribution of residual stress across the weld was observed in both cases. An additional qualitative analysis on the transverse distortion of the welds outlined a pronounced undesired "V-like" deformation of the HYB joint of approximately 1.4°. By contrast, the FSW joint seemed not to show any perceptible bend. Graphical abstarct: Image, graphical abstract